Memperkuat Kompetensi Servant Leadership melalui Pelatihan Seven Habits : Studi Pengembangan Kepemimpinan Transformatif bagi Suster Muda OSF di Kota Semarang - Nerita Setyaningtyas; Antonius Denny Firmanto; FR. Wuriningsih (Institut Teknologi dan Bisnis Semarang, 2025)
This community service program aims to develop servant leadership competencies for young sisters of the Order of Saint Francis (OSF) in Semarang City through seven habits training. Using a methodological approach that integrates andragogical principles and Franciscan spirituality, the program involved 25 young OSF sisters. The results show significant transformation in three competency areas: conceptual understanding of servant leadership, practical leadership skills, and reflective capacity. Evaluation reveals the effectiveness of integrating Franciscan spirituality, servant leadership principles, and the seven habits framework in creating a contextual leadership development model. This program makes an important contribution to developing transformative leadership training models for religious communities